A comparative study of code blue records. Issue 5 (September 2015) - Whitcomb, John J.; Hahn, Cayla; Sumner, Ivey; Shelley, Kirk; Hunnicutt, Taylor
<x xml:space="preserve">Abstract</x> Data collected in the ICU and CCU, from a cardiac arrest sheet and a handheld electronic device, were compared for 3 months. This study reviewed which of the two techniques most accurately captured code blue events.